Arequipa and the catalytic revolution of the urban space between 1868 and 1940 - Zeballos Velarde, Carlos (2023)
Urban catalysis is the process in which an element of the city – building or public space – generates a multiplying impact on the characteristics and roles of other surrounding elements. This article explores the catalytic effect that the transformation of the Plaza de Armas meant for Arequipa after the earthquake of 1868 and the consequences it had on other surrounding spaces, as well as on the architecture and on the perception of the urban landscape by the inhabitants of that area. epoch. The hygienic ideas, brought by English and Italian immigrants after the construction of the railway, promoted a revolution in the way of experimenting and constructing urban space, moving from a utilitarian vision of a rural colonial town to the deliberate construction of a modern garden city. in the middle of the desert. For this research, the study of primary and secondary sources, such as documentary and photographic review, is integrated with the analysis of spatial syntax and 3D modeling to be able to reconstruct the characteristics of these scenarios.